Membrane progesterone receptor induces meiosis in Xenopus oocytes through endocytosis into signaling endosomes and interaction with APPL1 and Akt2 - Nader, Nancy (PLoS Biol, 2020)
The steroid hormone progesterone (P4) mediates many physiological processes through either nuclear receptors that modulate gene expression or membrane P4 receptors (mPRs) that mediate nongenomic signaling. mPR signaling remains poorly understood. Here we show that the topology of mPRβ is similar to adiponectin receptors and opposite to that of G-protein-coupled receptors (GPCRs). Using Xenopus oocyte meiosis as a well-established physiological readout of nongenomic P4 signaling, we demonstrate that mPRβ signaling requires the adaptor protein APPL1 and the kinase Akt2. We further show that P4 induces clathrin-dependent endocytosis of mPRβ into signaling endosome, where mPR interacts transiently with APPL1 and Akt2 to induce meiosis. Our findings outline the early steps involved in mPR signaling and expand the spectrum of mPR signaling through the multitude of pathways involving APPL1.